Análise preliminar dos riscos ambientais e mecânicos: estudo de caso em uma indústria de ourivesaria na cidade de Abaetetuba-Pará - SILVA, Luciana Lobato (2024)
Environmental risks, safety mechanical and are three factors of importance to the improvement of the different types of organization, whether in the performance of functions of their workers as well as the impact on the surrounding environment of the industry. This study aimed to prepare an analysis of the risks of workers in a jewelry industry in the city of Pa-Abaetetuba propose improvements necessary in order to adapt the workplace to the standards of health and safety of the work force in the country. The method consisted of collecting data from on-site observation, interviews and photographic report. The study was based on the application of a risk management tool known as the Preliminary Risk Assessment (PRA) of activity Goldsmith. This tool is to show that some basic measures such as knowledge of the risks and damage they may cause, and measures for its prevention are opportunities to improve the working condition.